FINANCING SHIPPING MARKET: SPECIAL CHARACTERISTICS AND THE IMPACT OF BASEL III - SAMBRACOS, Evangelos; MANIATI, Marina (Journal of Advanced Studies in Finance; Vol 4 No 2 (2013): JASF Volume IV, Issue 2(8), Winter, 2013, 2013)
Shipping sector constitutes a sector with special characteristics that considerably differentiate it from the other sub-sectors of international transport. The maximization of benefits for each one of the special market characteristics form a highly dynamic environment, with high risk of loss of invested capital. Within this framework, commercial banks, being the main source of financing shipping market, which is characterized by high capital and operating costs, have to take into account various variables in order to minimize the risk and maximize the return. The last is of particular importance considering the recent regulatory framework for banks applied by the Basel III, which has been elaborated on the grounds of inappropriateness of Basel II.